2023
DOI: 10.1021/acs.est.2c08717
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Rubber Ozonation Explain the Effectiveness of 6PPD as an Antidegradant and the Mechanism of Its Quinone Formation

Abstract: The discovery that the commercial rubber antidegradant 6PPD reacts with ozone (O 3 ) to produce a highly toxic quinone (6PPDQ) spurred a significant research effort into nontoxic alternatives. This work has been hampered by lack of a detailed understanding of the mechanism of protection that 6PPD affords rubber compounds against ozone. Herein, we report highlevel density functional theory studies into early steps of rubber and PPD (p-phenylenediamine) ozonation, identifying key steps that contribute to the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 132 publications
1
4
0
Order By: Relevance
“…The majority of transformation products were consistent with highly oxidized quinone ring-opening products, which is consistent with previous observations of 6PPDQ transformation in the presence of ozone . Considering previous mechanistic insight from Rossomme et al, who assessed 6PPD transformation to 6PPDQ, we believe the central quinone ring system of 6PPDQ is rapidly oxidized by pathways exclusive of ozone, such as aqueous reactive oxygen species. Interestingly, an unknown C 21 H 26 N 2 O 5 transformation product was detected in both positive and negative mode.…”
Section: Resultssupporting
confidence: 91%
“…The majority of transformation products were consistent with highly oxidized quinone ring-opening products, which is consistent with previous observations of 6PPDQ transformation in the presence of ozone . Considering previous mechanistic insight from Rossomme et al, who assessed 6PPD transformation to 6PPDQ, we believe the central quinone ring system of 6PPDQ is rapidly oxidized by pathways exclusive of ozone, such as aqueous reactive oxygen species. Interestingly, an unknown C 21 H 26 N 2 O 5 transformation product was detected in both positive and negative mode.…”
Section: Resultssupporting
confidence: 91%
“…The majority of transformation products were consistent with highly oxidized quinone ring opening products, which is consistent with previous observations of 6PPDQ transformation in the presence of ozone. 29 Considering previous mechanistic insight from Rossomme et al, who assessed 6PPD transformation to 6PPDQ 30 , we believe the central quinone ring system of 6PPDQ is rapidly oxidized by pathways exclusive of ozone, such as aqueous reactive oxygen species. Interestingly, an unknown C21H26N2O5 transformation product was https://doi.org/10.26434/chemrxiv-2023-0mnh8 ORCID: https://orcid.org/0000-0002-4158-524X Content not peer-reviewed by ChemRxiv.…”
Section: Photoproducts and Proposed Degradation Pathwaysmentioning
confidence: 87%
“…N,N′ -Substituted p -phenylenediamines (PPDs) are a broad range of anthropogenic chemicals that have been extensively used as antioxidants in the rubber industry due to their superior capacity in protecting rubber products. Among these, N -(1,3-dimethylbutyl)- N′ -phenyl- p -phenylenediamine (6PPD), as the most frequently used antioxidant, has been listed as a high production volume (HPV) chemical . The annual production of 6PPD alone in China and the U.S. exceeded 20 and 50 million tons in 2020. , Other PPDs, such as N -isopropyl- N′ -phenyl-1,4-phenylenediamine (IPPD), N,N′ -diphenyl- p -phenylenediamine (DPPD), and N,N′ -ditolyl- p -phenylenediamine (DTPD), are also regarded as HPV chemicals with substantial annual productions. However, massive production and consumption have resulted in incredible emissions of PPDs into the environment. The growing evidence indicated that PPDs and related degradation products were ubiquitously detected in urban runoff, sediments, , airborne particles, , and even in human specimens (urine and blood) including sensitive populations (children and pregnant women), , attracting considerable concern regarding their potential risks to the environment and human health.…”
Section: Introductionmentioning
confidence: 99%